Laman dan Reputasi Lembaga Dalam Membangun Komunikasi dengan Stakeholders - Mukaromah, Mukaromah; Purnamasari, Devi (Jurnal The Messenger, 2016)
Page is one of the means of communication for a institute that can not be inevitable in the current  development of information technology today. The purpose of this study was to find out how the reader's perception of the website educational institutions in communicating their vision and mission. Using the method of qualitative descriptive study the research object Udinus page readers Semarang who are stakeholders. The results of the study reflect on the reader's perception of the page that conveys that reflect Udinus page as a page that is engaged in the field of education with the reputation of the institution which is prominent in the field of information technology. There needs to be improvement in conveying information in the field of entrepreneurship because the eyes of the readers who become informants in this research, news and events related to entrepreneurship has not been managed properly.